Triple-serotype chimeric oncolytic adenovirus exerts multiple synergistic mechanisms against solid tumors. Issue 5 (24th May 2022) - Su, Yinghan; Li, Jiang; Ji, Weidan; Wang, Gang; Fang, Lin; Zhang, Qin; Ang, Lin; Zhao, Min; Sen, Yuan; Chen, Lei; Zheng, Junnian; Su, Changqing; et al.
Abstract : Background: Oncolytic virotherapy has become an important branch of cancer immunotherapy. This study investigated the efficacy of an oncolytic adenovirus (OAV), OncoViron, with synergistic mechanisms in the treatment of multiple solid tumors. Methods: An OAV, OncoViron, was constructed and investigated by cytological experiments and implanted tumor models of multiple solid tumor cell lines to certify its anticancer efficacy, the synergistic effects of viral oncolysis and transgene anticancer activity of OncoViron, as well as oncolytic virotherapy combined with immunotherapy, were also verified. Results: The selective replication of OncoViron mediated high expression of anticancer factors, specifically targeted a variety of solid tumors and significantly inhibited cancer cell proliferation. On a variety of implanted solid tumor models in immunodeficient mice, immunocompetent mice, and humanized mice, OncoViron showed great anticancer effects on its own and in combination with programmed death 1 (PD-1) antibody and chimeric antigen receptor (CAR) T cells. Pathological examination, single-cell sequencing, and spatial transcriptome analysis of animal implanted tumor specimens confirmed that OncoViron significantly altered the gene expression profile of infected cancer cells, not only recruiting a large number of lymphocytes, natural killer cells, and mononuclear macrophages into tumor microenvironment (TME) and activated immune cells, especially T cells but also inducing M1 polarization of macrophages and promoting the release of more immune cytokines, thereby remodeling the TME for coordinating PD-1 antibody or CAR T therapy. Conclusions: The chimeric OncoViron is a novel broad-spectrum anticancer product with multiple mechanisms of synergistic and potentiated immunotherapy, creating a good opportunity for combined immunotherapy against solid tumors.